Valuation considerations of stock based compensation: a case study of semiconductor firms - Engel, Russell; Lyons, Bridget (Journal of Accounting and Finance, 2025)
Equity research analysts and investors remain divided on the treatment of stock-based compensation (SBC) in firm valuation, particularly in discounted cash flow (DCF) and earnings multiples techniques. Many firms and analysts exclude SBC, viewing it as a non-cash expense, while others argue this leads to overvaluation. SBC usage is especially high in the tech sector. This study examines five large semiconductor firms, analyzing SBC levels, its treatment in adjusted earnings, and its impact on share dilution, valuation multiples, and free cash flow calculations. Findings indicate that SBC treatment significantly affects valuation, particularly within the semiconductor industry.
Keywords: Accounting; Actuarial science; Business; Econometrics; Economics; Engineering; Finance; Financial economics; Stock (firearms); Stock options; Valuation (finance); dept.acc

Generalist CEOs and operational efficiency - Chung, Hanyong (Finance research letters, 2025)
Keywords: Accounting; Board of directors; Business; Economics; Firm size; Generalist CEO; Generalist and specialist species; Operational efficiency; dept.acc; peer-reviewed

Local Government Sustainable Development: A Theoretical Paradigm or a Plan for Action? - Phillips, Janet F.; Strickland, Pamela (Journal of Accounting, Ethics and Public Policy, 2015)
Local governments are a vital component in the national effort to promote sensible methods for community development, growth and social justice. The benefits and challenges of sustainable development have become apparent as more local governments initiate programs to address economic, environmental and social equity issues. This research investigates county and municipal government efforts toward sustainable development using survey information for local governments in the southern United States. Survey responses were analyzed to examine whether local governments “practice what they preach” in terms of actually implementing the sustainable policies proclaimed to be important to their operations. Overall, results suggest local governments do place these policies into action for environmental and social justice issues. In addition, the analysis explores the impact of population size, geographic area and form of government on sustainable development. Measuring the implementation of sustainable policies in terms of dollars, however, proves difficult because there is no consistency among municipalities with regard to reporting the amount of dollars (federal or local) spent in support of sustainability efforts.
Keywords: dept.acc; economic development; environmental protection; local government; peer-reviewed; social equity; sustainability

Accounting Majors Finish First – Results of a Five-Year Study of Performance in Introductory Accounting - Phillips, Janet F. (The Accounting Educators' Journal, 2015)
Delivery of a quality introductory accounting course is essential for schools of business. The first step in revitalization and improvement of the course is to identify factors suggested to be empirically related to succeessful completion. Accounting major status is of particular interest. While it has long been anecdotally observed and logically expected that accounting majors would earn higher grades in introductory accounting, it is rarely addressed in empirical studies. To investigate the impact of accounting major status on performance in introductory accounting, a sample of 398 students exposed to the same professor, text, teaching and examination format over five-years was gathered. Results suggest accounting major status was in fact a significant positive predictor of grades earned in the class controlling for three additional variables (i.e., grade point average, mathematics background and previous experience in the course). These results could be used to support the creation of an honors section(s) of accounting which could include a more rigorous curriculum taught with real life cases. Previous research supported the concept of an honors program from students, faculty and potential employers. In addition, the results suggest requiring a minimum grade point average and the completion of mathematics requirement before taking introductory accounting.
Keywords: dept.acc; peer-reviewed

The GAAP in Tesla’s Earnings Announcements: A Case Study on the Proliferation of Non-GAAP Financial Measures - Aselta, James; Engel, Russell Paul (The Accounting Educators' Journal, 2018)
The reporting of non-Generally Accepted Accounting Principles Measures (non-GAAP) by U.S. publically traded companies is not new but it has recently come under increased scrutiny by the United States Securities and Exchange Commission (SEC). This case presents a specific example of this scrutiny in the form of Tesla, Inc.’s quarterly earnings announcements and Tesla’s subsequent correspondence with the SEC. This case requires students to answer relevant questions about GAAP vs Non GAAP reporting, generally in the form of a research memo, with references to applicable SEC regulations and guidance on the use and reporting of non-GAAP measures.
Keywords: dept.acc; peer-reviewed

Improving Student Performance in Introductory Accounting - Raising Minimum Grade Standards is Not the Answer - Phillips, Janet (The Accounting Educators' Journal, 2021)
An ongoing debate continues at universities surrounding whether or not to raise minimum grade standards. Because of an inherent risk that enrollments may decline as a result, it is important to examine whether minimum grade policies are associated with improved student performance. To address this issue, the current study examines the relationship between higher minimum grade requirements in introductory accounting and student grades. The new minimum grade requirement of â€œCâ€ was established beginning with the fall 2015 semester for introductory accounting to strengthen the quality of the program for an AACSB application. The research design included modeling introductory accounting grades over a ten-year period to examine any effect of the increase in the minimum grade on studentsâ€™ grades in the course. The multivariate regression equation considered variables previously found associated with introductory accounting grades (i.e., status as accounting major, grade point average, mathematics preparedness and previous experience taking the course). An additional dichotomous variable was introduced to capture the impact of students on the new program. All students were taught by the same professor, using the same textbook, teaching philosophy and examination format to enhance the comparison. Results suggest average grades in introductory accounting did not improve as expected.
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

An Examination of the Relationship Between the Funded Status of Defined Benefit Pension Plans and the Financial Condition of Sponsoring Organizations – Public Vs Private Sector - Phillips, Janet F. (Journal of Accounting Ethics and Public Policy, 2022)
Defined benefit pension plans are a bedrock of the U.S. economy providing guaranteed payment streams at pre-established amounts. Results suggest public plans, sponsored by State and Local governments, and private plans, sponsored by public corporations, are unfunded. State plans were found to have the largest pension and unfunded pension liabilities. Examination of relationships between unfunded pension liabilities and fiscal or financial stability of sponsoring organizations suggests unfunded State pension plans are more likely to be sponsored by financially struggling sponsors measured by general obligation bond ratings. Local governments and Corporations with unfunded pension plans are less likely to be struggling financially. Fiscal distress of Local governments was measured by survival analysis. Corporation financial distress was quantified by a model designed to predict bankruptcy. Financially stable organizations failing to fund pension plans, in this case local governments and corporations, suggests a lack of social responsibility.
Keywords: Defined benefit pension plans; dept.acc; financial or fiscal distress; peer-reviewed; social responsibility; unfunded pension liabilities; ⛔ No DOI found

How to Handle Pressure to Act Unethically - Haylon, Lisa S.; Bishop, Carol C.; Boyle, Douglas M.; Hermanson, Dana R. (Management Accounting Quarterly, 2022)
It is likely that accountants will face pressure to act unethically during their careers. We offer 10 practical steps to help financial professionals prepare for and respond to the pressure to act unethically.
Keywords: Accounting; Business And Economics--Accounting; Business And Economics--Management; Business ethics; Compliance; Conformity; Decision making; Fraud; Management accountants; Personality; Professionals; dept.acc; peer-reviewed; ⛔ No DOI found

A data analytics mindset with Crisp-Dm - O'Hara, Richard; Haylon, Lisa S.; Boyle, Douglas M. (Strategic Finance, 2023)
According to a 2020 survey of 600 senior executives conducted by Harvard Business Review, 55% of organizations agreed that data analytics for decision making is extremely important and 92% asserted data analytics for decision making will be even more important in two years (bit.ly/3PBRENs). Organizations that strategically deploy tools across their finance and accounting functions have an opportunity to better structure manual processes into more stable, accurate, repeatable, and readily auditable procedures (see Gregory Kogan, Nathan Myers, Daniel J. Gaydon, and Douglas M. Boyle, "Advancing Digital Transformation," Strategic Finance, December 2021, bit.ly/3V45v0h). [...]financial decision makers are increasingly expected to engage data analytics to enhance decision making and create more efficient processes. Deployment/communication It's very important to assign responsibilities to team members (e.g., business analysts establish requirements, IT specialists gather required data, and data scientists develop and test advanced modeling techniques) with the requisite skills that vary among the phases. [...]unstructured data is data that has no uniform structure and typically isn't text-based, for example, image or sound files.
Keywords: Business And Economics--Accounting; Data analysis; Data mining; Decision making; Decision support systems; Enterprise resource planning; Management accounting; dept.acc; peer-reviewed; ⛔ No DOI found

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found

Using an Ounce of Prevention - Does It Reduce Health Care Expenditures and Rea; Pound of Profits: A Study of the Financial Impact of Wellness and Health Risk Screening Programs. - Phillips, Janet (2008)
Keywords: dept.acc; faculty_collection; sabbatical_report

International Accounting Standards Committee: A Political History. - Kirsch, Robert (2000)
Keywords: dept.acc; faculty_collection; sabbatical_report

Struggling for - Profit Hospitals Sink Further After Sale to Not-for-Profit Owners. - Phillips, Janet (Spring;Accounting., 2000)
Keywords: dept.acc; faculty_collection; sabbatical_report

Indelible Footprints: The ICAN Story - Olutimehin, Kola; Emenyonu, Emmanuel (ICON, 2015)
Keywords: History; History; Accounting; Institute of Chartered Accountants of Nigeria; Nigeria; dept.acc; faculty_collection

Winning by His Grace: The Biography of Felix Ohiwerei - Emenyonu, Emmanuel (The Washington Nigerian Times, 2012)
Keywords: Biography; Christian biography; Biography; Nigerians; Nigeria; Ohiwerei, Felix; Businessmen; dept.acc; faculty_collection

Goatskin Bags and Wisdom: New Critical Perspectives on African Literature - Emenyo̲nu, Ernest (Africa World Press, 2000)
Keywords: Africa; African literature; Appreciation; Criticism; History and criticism; African literature; History; National characteristics, African; Africans; Race identity; dept.acc; faculty_collection

Practices in concurrent engineering - Ellis, L.W.; Curtis, C.C. (Institute of Electrical and Electronics Engineers Inc., 1992)
To describe concurrent engineering, one must remember the old story of blind individuals attempting to characterize an elephant by feeling different body parts. The issue seems not to be just R&D cycle times, but the entire innovation cycle time process from conception of an idea ~ often in marketing not R&D -, to its final delivery to a customer - often through down-stream firms not under the R&D company's control. From the recency of many sources in the literature, this shift to a time orientation is itself rather recent. Two threads seem to have emerged: First, there is a need to address cycle-time reduction on existing products and services, both in manufacturing and administration, as an implementation management issue relating to the order-to-delivery cycle, in which engineering may be a limited associate. Also, necessary is the innovation management issue of reducing the cycle time from marketing concept to proquct introduction into the implementation process, which is the main thrust of concurrent engineering. In late 1991, a survey was conducted, first, to seek to establish a better working definition of cycle time within the two overall areas of current operations and new product development, and second, to determine the relationships between cycle time so defined and company size or profitability. The survey questionnaire was mailed to 99 medium-to-large high technology manufacturing companies in Connecticut, and yielded 48 responses, with 35 of them usable. The results confirmed the impression given by the literature that the concept was better established in current operations than in innovation management. While some do use the concept of cycle time in their new product development sub-cycles, most do not track time spent on either end of the cycle, from idea to design on the near end, or at the far end through shipment and subsequent service to the customer. Measures of size did not correlate with any of the development measures, while they did with some of the operations measures. Thus, while in concept, concurrent engineering appears to be a goal of multi-functional co-operation, a survey of the manner in which a limited number of firms actually operate seems still focused on functional specializations. © 1992 IEEE.
Keywords: Commerce; Concurrent engineering; Cycle time reduction; Environmental management; Implementation managements; Implementation process; Innovation management; Manufacturing companies; Marketing; Marketing concept; New product development; Product design; Product development; Products and services; Surveys; dept.acc

Audit effectiveness preceding bankruptcy in UK financial institutions - Malgwi, C.A.; Emenyonu, E.N. (International Journal of Accounting, Auditing and Performance Evaluation, 2004)
This study investigates audit effectiveness (or the lack thereof) of audit opinions issued by auditors preceding company bankruptcies. Data from all 26 bankrupt UK financial institutions were used to determine if auditor appropriately issued opinions other than unqualified, as signs of non-going concern determine any differences in audit-opinion effectiveness between international and domestic audit firms. Results show that unqualified opinions issued was significantly higher than other opinions prior to bankruptcy. While international audit firms were less likely to issue unqualified opinions than their domestic counterparts no firm issued adverse or disclaimer of opinions in any given year, despite serious warning signals from return on assets (ROA), return on equity (ROE) and current ratios. © 2004 Inderscience Enterprises Ltd.
Keywords: audit effectiveness; audit opinion; bankruptcy; dept.acc; financial institutions; going concern

The evolution of the relationship between the us financial accounting standards board and the international accounting standard setters: 1973-2008 - Kirsch, R.J. (Accounting Historians Journal, 2012)
Utilizing archival materials as well as personal interviews and correspondence with personnel of the Financial Accounting Standards Board (FASB) and International Accounting Standards Committee /Board (IASC/B), including former Board chairmen and staff members, this paper examines the development of the working relationships between the FASB and the IASC/B from their earliest interactions in 1973 through the transformation of the IASC into the IASB and the Convergence Program rooted in the 2002 Norwalk Agreement up to 2008. © 2012, Academy of Accounting Historians. All rights reserved.
Keywords: dept.acc

Railroad audits: Some arrived ahead of schedule - Feeney, K. (Accounting Historians Journal, 2013)
Through 1975, the shareholder annual reports of publicly-owned U.S. railroads were exempt from the Securities and Exchange Commission’s accounting regulations, audit and disclosure rules because railroads were common carriers subject to the rules and regulations of the Interstate Commerce Commission (ICC). Pub-liclyowned Class railroads voluntary began to away from ICC-type towards GAAP-type accounting and disclosures in their shareholder reports just after World War II.1 This paper reviews early industry practices with respect to internal and external audits. Using a sample of major Class I railroads from 1946 to 1975, the paper shows: the extent to which certain railroads voluntarily presented audited finan-cial statements before being required, the extent to which particular CPA firms were involved with the railroad industry, and the types of audit reports that issued to these railroads during this period. © 2016, Academy of Accounting Historians. All rights reserved.
Keywords: dept.acc

The role of non-governmental organizations (NGOs) as intermediaries of the European union decision to adopt international accounting standards: 1973-2002 - Kaya, D.; Kirsch, R.J.; Henselmann, K. (Accounting Historians Journal, 2016)
This paper analyzes the role of non-governmental organizations (NGOs) as intermediaries in encouraging the European Union (EU) to adopt International Accounting Standards (IAS). Our analysis begins with the 1973 founding of the International Accounting Standards Committee (IASC), and ends with 2002 when the binding EU regulation was approved. We document the many pathways of interaction between European supranational, governmental bodies and the IASC/IASB, as well as important regional NGOs, such as the Union Européenne des Experts Comptables, Économiques et Financiers (UEC), the Groupe d’Etudes des Experts Comptables de la Communauté Économique Européenne (Groupe d’Etudes), and their successor, the Fédération des Experts Comptables Européens (FEE). This study investigates, through personal interviews of key individuals involved in making the history of the organizations studied, and an extensive set of primary sources, how NGOs filled key roles in the process of harmonization of international accounting standards. © 2016, American Accounting Association. All rights reserved.
Keywords: dept.acc

Using an ounce of prevention: does it reduce health care expenditures and reap pounds of profits? A study of the financial impact of wellness and health risk screening programs. - Phillips, Janet F (Journal of health care finance, 2009)
As we are all well aware, health care expenditures in the United States are out of control and growing at epic proportions. Since private industry shoulders a significant burden of paying these rising health care costs, the huge and ever increasing sum paid by these corporations continues to impact the US economy translating into higher prices of services and manufactured goods and reduced job opportunities when companies outsource jobs or locate manufacturing facilities to avoid paying health care benefits for workers. As a result, health care expenditures have become a centerpiece of an enormous public policy debate as Congress is currently working on several versions of a bill to completely revise health care from the ground up. This research project was accomplished to examine the effectiveness of one approach to control rising health care costs and contain corporate financial responsibility--the establishment of wellness and health risk screening programs to improve the health of employees. Total health care cost per insured individual was gathered through an online survey directly from health care benefit administrators. The survey also asked information about wellness and health risk screening programs and the related responses were used to determine if there were a relationship between health care costs and health prevention programs. While statistical analysis was hampered in the current study because of the small sample size, some valid conclusions were reached. The study was successful in identifying a benchmark of Average Total Health Care Cost per Individual from $5,100 to $5,800 for 2005 through 2007. This is especially interesting in light of the fact that an average of $7,026 was spent on health care per person in 2006 in the United States. The study was also able to contribute an estimate of the increase realized in these expenditures of 6 percent in 2007 over 2006, and 4 percent in 2006 over 2005, which were in fact similar to the national average. The final contribution of the study is to suggest an explanation for the costs which appear to be holding their own in terms of the national average. While this cannot be statistically verified, it does seem that the active participation of these companies in wellness programs could be a factor. Wellness programs were very popular in this sample of companies as 82 percent of the respondents answered "YES" when asked if the company funds their own employee wellness program. This is an impressive number of companies that have recognized wellness programs as a potential means to reduce employee health care costs. In regards to specific programs, at least 50 percent of respondents answered that they have smoking cessation, employee fitness, counseling, health risk screening, and bio-metric screening programs. The existence of health screening variables show an impressive 73 percent of respondents do practice some sort of health care screening, 50 percent offer biometric screening while 18 percent have onsite clinics and 23 percent run annual employee fairs.
Keywords: *Health Care Costs/td [Trends]; *Health Expenditures; *Health Promotion/ec [Economics]; *Occupational Health Services/ec [Economics]; Cost-Benefit Analysis; Health Care Costs; Health Expenditures; Health Promotion; Health risk screening program; Humans; Mass Screening; Mass Screening/ec [Economics]; Occupational Health Services; Preventative health programs; Risk Assessment; Risk Assessment/ec [Economics]; United States; Wellness program; article; biometry; dept.acc; employee; financial management; fitness; funding; government; health care cost; health care financing; health care industry; health care policy; health hazard; occupational health service; patient counseling; preventive health service; profit; responsibility; risk assessment; smoking cessation; wellbeing; ⛔ No DOI found

Do managerial efficiency and social responsibility drive long-term financial performance of not-for-profit hospitals before acquisition?. - Phillips, J F (Journal of health care finance, 1999)
Due to steep declines in charitable support and reduced demand for traditional hospital services, economic goals are increasingly important to not-for-profit hospitals. Effects of efficient management and effective pursuit of not-for-profit status (for example, levels of Medicare, indigent patients, and unprofitable services) on financial viability are explored. While previous research compared hospitals of different ownership status, not-for-profit hospital operations before acquisition by for-profit hospital chains are investigated--"neutral ground" relative to ownership. Results suggest minor links between efficiency and long-term profitability despite effectiveness in pursuit of non taxable status.
Keywords: *Efficiency, Organizational; *Financial Management, Hospital; *Hospitals, Voluntary/og [Organization & Administration]; *Social Responsibility; Bed Occupancy; Case mix index; Diagnosis-Related Groups; Efficiency, Organizational; Financial Management, Hospital; Free cash flow accounting valuation; Health Facility Merger; Health Facility Merger/sn [Statistics & Numerical Data]; Hospitals, Voluntary; Hospitals, Voluntary/st [Standards]; Humans; Investor-owned hospital corporations; Least-Squares Analysis; Length of Stay; Length of stay; Managerial efficiency; Median household income; Medicare; Medicare patients; Medicare/sn [Statistics & Numerical Data]; Not-for-profit hospital acquisitions; Occupancy rate; Social Responsibility; Social responsibility; United States; article; dept.acc; financial management; hospital finance; hospital management; hospitalization; length of stay; medicare; profit; social behavior; ⛔ No DOI found

Satisfy customers while speeding R&D and staying profitable - Curtis, Carey C; Ellis, Lynn W (Research-technology Management, 1998)
Studies of innovation management effectiveness pinpoint specific practices that will allow companies to increase customer satisfaction and pursue a strategy of speedy R&D-without compromising profitability. The two practices that accomplish this end, when used moderately (although not universally), are Quality Function Deployment for project selection and Stage-Gate Tracking for controlling development. Companies that use Internal Rate of Return as a criterion for project selection have also been found to be move profitable.
Keywords: Customer satisfaction; Industrial economics; Profitability; Quality function deployment; Research and development management; Strategic planning; dept.acc

The influence of career stage on the work attitudes of male and female accounting professionals - Lynn, Susan A; Cao, Le Thi; Horn, Betty C (Journal of Organizational Behavior, 1996)
The present study compared work commitments, overall job satisfaction, intrinsic and extrinsic rewards satisfactions, and organizational and professional turnover intentions of 718 male and female accounting professionals at different career stages. Career stage was measured by professional tenure. The results indicate that there are some differences in work attitudes across career stages for male accounting professionals. Job involvement, organizational commitment, and intrinsic and extrinsic rewards satisfaction are positively related to professional tenure. Organizational turnover intentions are negatively related to professional tenure for male accounting professionals. There are no significant differences in work attitudes across career stages for female accounting professionals, An examination of reasons for differences in work attitude patterns between male and female accountants suggests the need for research to determine whether later career stages (advancement and maintenance) differ for men and women. The results also suggest that future research should consider defining career stage in terms of the overlap between stages defined using alternate career stage measures.
Keywords: dept.acc

The nigerian financial superstructure, financial intermediation, and environmental factors: issues, empirical evidence, and managerial implications - Ezirim, Chinedu B; Muoghalu, Michael I; Emenyonu, Emmanuel (Journal of African Business, 2004)
The paper empirically investigates the extent to which environmental factors affect the intermediation performance of the financial superstructure in Nigeria. A number of intermediation-environmental models were constructed and estimated against annual Nigerian data from 1970 to 2000. Among the various environments of financial intermediation, the socio-political environment, the regulatory environment, and the eco-financial environment exert very great influences on the operations of the financial superstructure. This is based on the evidence from the results, which revealed the socio-political index, regulatory index, and foreign exchange market variables as the most critical predictors of the financial intermediation-output-related index. Other factors such as inflation, taxation, financial market imperfection, and the growth rate of the economy appear not to exert statistically significant effects on the intermediation operations of the financial superstructure. Generally, the utility of the specified models was satisfied as indicated by the results of the global statistics. © 2004 by The Haworth Press, Inc. All rigths reserved.
Keywords: Africa; Eastern Hemisphere; Environmental factors; Financial institutions; Financial intermediation; Financial markets; Financial superstructure; Financial system; Nigeria; Sub-Saharan Africa; West Africa; World; dept.acc; growth rate; management practice; market conditions; performance assessment

Investing in R&D: How to manage your risk - Curtis, Carey C (Journal of Corporate Accounting & Finance, 2001)
Keywords: dept.acc

The entry of international CPA firms into emerging markets: motivational factors and growth strategies - Kirsch, Robert J; Laird, Kenneth R; Evans, Thomas G (The International Journal of Accounting, 2000)
This article examines the entry of professional service firms, specifically the Big Six international accounting firms, into emerging foreign markets and explores how they develop and expand their business once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. A conceptual model is employed to illustrate the interrelationship between a firm's specific characteristics, the foreign environment, and foreign subsidiary intrafirm structure. Growth potential, client needs, favorable political/legal climate, and cultural considerations emerged as important factors in determining market entry and growth strategies for professional services firms. The research findings broaden our understanding of factors that influence professional services firms' development of pricing and marketing mix strategies. While all firms surveyed offered a full range of services, their marketing mix strategy differed from domestic approaches because of various local constraints on pricing and promotion. Copyright © 2000 University of Illinois.
Keywords: Commonwealth of independent States; Eastern European and Baltic States; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt

A marketing resource-based model of international market entry and expansion for professional services firms - Laird, Kenneth R; Kirsch, Robert J; Evans, Thomas G (Services Marketing Quarterly, 2003)
This paper examines the entry of the Big Six international accounting firms, into emerging foreign markets and explores marketing resource considerations once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. The paper presents a marketing resource-based model based upon relevant research. The model focuses on firm specific resource capabilities interacting with the foreign business environment and the foreign intrafirm structure as a determinant of foreign market entry choice and eventual market expansion. The research findings broaden our understanding of factors that influence professional services firms' development of marketing resource strategies when expanding globally. While all firms surveyed offered a full range of services, their marketing resource strategy differed from domestic approaches because of various local constraints on marketing mix elements. © 2003 Taylor & Francis Group, LLC.
Keywords: Commonwealth of Independent States; Eastern European and Baltic states; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt

Intermediation behavior of the financial superstructure in response to environmental stimuli: theory, issues and further empirical evidence from nigeria - Ezirim, Chinedu B; Muoghalu, Michael I; Emenyonu, Emmanuel (Journal of African Business, 2007)
This paper is an empirical extension aimed at investigating the relationships between the indicators of the financial superstructure and its intermediation environments; and especially how the former responds to the effects of the latter. Intermediation-environmental models patterned after multivariate regression, causality, and partial adjustment models of both linear and log-linear formulations were estimated and analyzed. The results reveal that three environments: socio-political, regulatory, and international finance-exerted significant effects on the intermediation function of the superstructure. Previous intermediation successes ginger up current performance. In the long run, the effects of the environmental factors on the intermediation function of the superstructure, in whatever direction, more than quadruples. In any given year, the Nigerian financial superstructure attains only about 21.9% of desired (optimal) FIR. Given this, it would take about 4-1/2 years for it to adjust its intermediation operations (FIR), in light of the effects of environmental factors, to optimal levels in order to significantly impact the economy as desired. Some consistent behavioral traits were identified from the results to include: the precepts of potential maximization, profit maximization, accommodation principles, survival and cost-minimization principles, and the neutrality axiom. © 2007 by The Haworth Press, Inc. All rights reserved.
Keywords: Africa; Eco-financial environments; Environmental Stimuli; Financial Superstructure; Intermediation Behavior; International financial environments; Nigeria; Regulatory environments; Socio-political environments; Sub-Saharan Africa; West Africa; Zingiber officinale; behavioral response; dept.acc; economic structure; empirical analysis; finance; modeling; regression analysis; socioeconomic impact; theoretical study

The GAAP in Tesla’s earnings announcements: A case study on the proliferation of Non-GAAP financial measures - Aselta, James; Engel, Russell Paul (The Accounting Educators' Journal, 2019)
The reporting of non-Generally Accepted Accounting Principles Measures (non-GAAP) by U.S. publically traded companies is not new but it has recently come under increased scrutiny by the United States Securities and Exchange Commission (SEC). This case presents a specific example of this scrutiny in the form of Tesla, Inc.’s quarterly earnings announcements and Tesla’s subsequent correspondence with the SEC. This case requires students to answer relevant questions about GAAP vs Non GAAP reporting, generally in the form of a research memo, with references to applicable SEC regulations and guidance on the use and reporting of non-GAAP measures.
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found